SPEECH VERBALIZATIONOF NLP TECHNIQUES AS AN SUBJECT OF LINGUISTIC RESEARCH - Akateva, I.S. (Bulletin of Udmurt University. Series History and Philology, 2020)
The range of issues raised in this article is related to the interdisciplinary approach to scientific researches and the possibility of combining of various Humanities in order to develop strategies and tactics aimed at qualitative positive changes in the state of cognitive structures of a person, the preservation and improvement of his mental and physical health. The article deals with the variants of speech actualization of the reframing technique used in neurolinguisticprogramming to improve the quality of life of the subject by changing the perception of the problem situation. The frame approach to the analysis is described as a general basis for the linguistic study of psychological practice. The structural-semantic and lexico-grammatical analysis of the variants of speech actualization of the reframing technique in a couple of "Problem Frame" - "OutcomeFrame" are conducted. The conclusions allow us to talk about the productivity of the frame approach in such analysis, as well as to determine the linguistic-cognitive and linguistic parameters of the success of such transformation.